The role of language in scaffolding content & language integration in CLIL science classrooms - Tang, Kok-Sing (2019)
This commentary to the special issue “Teaching, Learning and Scaffolding in CLIL Science Classrooms” synthesizes the contributions from the authors by addressing two overarching questions. First, what is the role of language in mediating science teaching and learning in a CLIL science classroom? Second, to what extent can content and language be integrated or separated in CLIL instruction and assessment? In addressing the first question, I distil three major perspectives of how the authors conceive the role of language as a scaffolding tool. These roles are: (a) providing the discursive means and structure for classroom interaction to occur, (b) enabling students’ construction of knowledge through cognitive and/or linguistic processes, and (c) providing the semantic relationships for science meaning-making. These three perspectives roughly correspond to the discursive, cognitive-linguistic, and semiotic roles of language respectively. In addition, two other roles – epistemic and affective, though not emphasized in this issue, are also discussed. In addressing the second question, I raise a dilemma concerning the integration of content and language. While there are clear political and theoretical arguments calling for an inseparable integration, there is also a common practice to separate content and language as distinct entities for various pedagogical and analytical purposes. In revolving this conundrum, I suggest a way forward is to consider the differences in the various roles of language (discursive/cognitive/linguistic vs. semiotic/epistemic/affective) or the levels of language involved (lexicogrammar vs. text/genre).